Set It and Forget It: The One-Way Use of Social Media by Government Agencies Communicating Science. (August 2015) - Lee, Nicole M.; VanDyke, Matthew S.
As traditional thinking about science communication is modified to emphasize engagement with science, public relations theorizing—particularly related to dialogic communication—may contribute to science communication theory and practice. Despite calls to move beyond the deficit model, we argue that many science organizations continue to practice one-way communication and underutilize social media's potential for dialogue. To support our argument, we provide data to illustrate how U.S. federal government science agencies use new media platforms for information dissemination rather than engagement. We call for a clearer integration of public relations theories and science communication models to inform communication best practices.